Investigating the Effects of Midwife-Oriented Education and Counseling on the Type and Consequences of Childbirth in First-Time Pregnant Women with Fear of Childbirth - Seyedeh Fatemeh Mosavi; Elham Jafari; Roghayeh Kharaghani; Saeedeh Zenoozian (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Fear of childbirth is one of the major problems during pregnancy and the post-partum period that affects women's health and preference for cesarean birth. Objectives: The present study aimed to investigate the effect of midwife-oriented education and counseling on the type and consequences of childbirth in first-time pregnant women with fear of childbirth. Methods: The present study is a single-blind randomized controlled trial performed on 122 first-time pregnant women with fear of childbirth. The samples were selected by the convenient sampling method and divided into two intervention and control groups by the four-blocked randomization method. Data collection tools were a demographic questionnaire and the Wijma Delivery Expectancy/Experience Questionnaire (WDEQ; version A before childbirth and version B after childbirth). The intervention was performed in the form of six counseling sessions based on the Gamble approach. The data were analyzed at a significance level of 0.05 using SPSS 21 statistical software. Results: Regarding the effect of midwife-oriented counseling on pre-partum and post-partum fear, no statistically significant difference was observed between the two groups. The rate of choosing vaginal birth in the intervention group significantly increased after receiving counseling (p = 0.001). The frequency of vaginal birth, childbirth satisfaction, and childbirth consequences was not statistically significant between the two groups. Conclusion: The present counseling method can be effective in increasing choosing vaginal birth in first-time pregnant women with fear of childbirth, but further research is required to evaluate its effectiveness on the maternal and neonatal consequences.